Perbandingan Kontribusi Pasar Uang, Pasar Modal, dan Pembangunan Sektor Riil di Indonesia dan Qatar dalam Perspektif Ekonomi Syariah: Studi Kualitatif Komparatif - Eza Okhy Awalia Br Nasution; Maryam Batubara (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze and compare the contribution of the money market, capital market, and real sector development in Indonesia and Qatar using a qualitative comparative approach. The research method employed is library research with secondary data obtained from official financial institution reports, government publications, and relevant academic journals. The findings indicate that the money market in both countries primarily functions as a liquidity stabilization and monetary policy instrument, while the capital market plays a key role in long-term financing of the real sector. Indonesia demonstrates a more dynamic and inclusive financial market development; however, it still faces challenges in effectively channeling funds into productive sectors. In contrast, Qatar has a more stable, concentrated, and investment-oriented financial system supported by sovereign wealth funds. From an Islamic economic perspective, Qatar shows a stronger integration between the financial sector and the real sector based on asset-backed principles. The study concludes that the effectiveness of financial sector contributions to the real sector is influenced by economic structure, financial system stability, and investment orientation in each country.